PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR PELAKSANAAN PENYULUHAN KETAHANAN PANGAN (BP2KP) LABUHANBATU SELATAN - Elvina, Elvina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
Work discipline and work experience are very decisive in the work performance process which aims to improve employee performance in carrying out the duties assigned to each employee. In this study, the object taken was the food security counseling office (BP2KP) in South Labuhanbatu, the data sources included primary and secondary data with the independent variable work discipline (X1), work experience (X2) with the dependent variable work performance. The population in this study were 66 respondents. While the sample taken is all of the total population, namely 66 respondents. The data analysis technique is a technique multiple linear regression. T test, F test and Determination. The results of the analysis using the statistical tool SPSS Ver. 20.0 obtained the results of the equation Multiple linear regression research is Y = 0.096 + 0.169.X1 + 0.815.X2. Based on the results research shows that the results of the variable work discipline on job performance then obtained, r count> r table or 1.766> 1.684. so that Ho was rejected and Ha accepted So in conclusion, there is a positive and significant effect of work discipline on work performance.Thus, r count> r table or 7,810> 1.684, Ho is rejected and Ha is accepted so the conclusion is that there is a positive and significant effect of work experience on work performance. While simultaneously (simultaneously) the influence of work discipline and work experience (F count = 104.245> F table = 3.11). The influence of both is quite strong with a correlation value of R = 0.771, positive and significant because if there is an improvement in work discipline and work experience, it will automatically relate to work performance (R2 = 0.771). The effect of work discipline and work experience is 77.1%, while 22.9% is influenced by other factors outside of this research model.